Elimination of D-lactate synthesis increases poly(3-hydroxybutyrate) and ethanol synthesis from glycerol and affects cofactor distribution in recombinant Escherichia coli - Nikel, P.I. (2010)
The effect of eliminating D-lactate synthesis in poly(3-hydroxybutyrate) (PHB)-accumulating recombinant Escherichia coli (K24K) was analyzed using glycerol as a substrate. K24KL, an ldhA derivative, produced more biomass and had altered carbon partitioning among the metabolic products, probably due to the increased availability of carbon precursors and reducing power. This resulted in a significant increase of PHB and ethanol synthesis and a decrease in acetate production. Cofactor measurements revealed that cultures of K24K and K24KL had a high intracellular NADPH content and that the NADPH/NADP+ ratio was higher than the NADH/NAD+ ratio. The ldhA mutation affected cofactor distribution, resulting in a more reduced intracellular state, mainly due to a further increase in NADPH/NADP+. In 60-h fed-batch cultures, K24KL reached 41.9 g · liter-1 biomass and accumulated PHB up to 63% ± 1% (wt/wt), with a PHB yield on glycerol of 0.41 ± 0.03 g · g-1, the highest reported using this substrate. © 2010, American Society for Microbiology.